Perception of nurses regarding risk classification in emergency care units - Carmen Lúcia Mottin Duro; Maria Alice Dias da Silva Lima; Patrícia Fátima Levandovski; Marcia Luciane da Silva Bohn; Kelly Piacheski de Abreu; Kelly Piacheski de Abreu (Rev Rene, 2014)
This study aimed to assess nurses’ perception regarding the risk classification in emergency care units. It is a descriptive study that used a qualitative approach and that was conducted with 55 nurses from emergency care units in the south of Brazil. Data were collected between July and October, 2011, through open questions, answered in writing. The data collected were submitted to the thematic analysis technique. Results indicate that the risk classification contributes to the organization of the service flow provided to patients, intervening in severe cases and preventing sequelae. Difficulties were described, such as: inadequate physical installations, overcrowding, disagreement in the definition of priorities among doctors and nurses and lack of articulation between the emergency care network and basic health care. It is highlighted the need to improve the physical structure, the quantity of human resources and the implementation of public policies to overcome these challenges.